Experimental Investigation of the Influence of Opening Dynamics on the Blast Overpressure Anisotropy in BLEVEs - El Mehdi Laamarti; Frederic Heymes; Clement Chanut; Albrecht Michael Birk (Chemical Engineering Transactions)
The Boiling Liquid Expanding Vapor Explosion (BLEVE) is one of the most dangerous industrial accidents, occurring when a pressure vessel containing a pressure liquefied gas like LPG or heated water suffers a catastrophic structural failure. Once the vessel opens, the vapor phase leaves the vessel pushing the surrounding atmosphere out of the way, leading to compression waves that then pile up to form a shock overpressure. The vessel progressively opens causing a rapid depressurization and violent boiling. A BLEVE results in many other hazards including projectiles, flammable or toxic release and ground loading. To date, many experiments have been carried out to predict the BLEVE hazards. Most of these studies have been performed with limited data on far-field overpressure and mainly focusing on the blast data measured on perpendicular horizontal directions. These studies showed that the blast shape is contingent upon vessel’s geometry; in cylindrical vessels the blast is not directionally uniform. This is also true for spherical vessels. Given that most industrial pressure vessels are cylindrical, this paper investigates blast overpressure resulting from top-initiated failures in cylindrical vessels, utilizing small-scale BLEVE experiments. The results indicated that the Top blast gauges recorded the highest overpressure, followed by the 45-degree angle and end gauges.